Performance of wrestlers at the Olympic Games: gender aspect - Curby, D.; Dokmanac, M.; Kerimov, F.; Tropin, Y.; Latyshev, M.; Bezkorovainyi, D.; Korobeynikov, G. (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim. With the increasing popularity of freestyle wrestling, the scientific community is paying more attention to gender factors that may influence the performance and success of competitive activities. The aim of study to determine differences in performance indicators between male and female wrestlers in the Olympic Games 2021.